Rapid one-of-a-kind product development strategies, algorithms and tools - Xie, Shane S. Q.; Tu, Yiliu; SpringerLink (Online service). (London New York Springer Verlag, 2011)
Rapid One-of-a-kind Product Development discusses research in the development of new enabling technologies for small and medium companies. Scientific advancements presented include a novel product data modelling scheme to model product design, manufacturability and knowledge under a common data object; customised product development in a distributed environment; and new adaptive scheduling methods for the optimal production of a wide variety of customised products, taking into consideration all of the possible changes from customers and the uncertainties in manufacturing. The book also includes research towards a computer aided customer interface, which allows customer requirements and changes to be processed and integrated with technical designs in real time; adaptive and concurrent CAD methods and algorithms; and product modelling and system integration technologies. The reader will learn how to: translate customer requirements to technical attributes; develop new and innovative products to meet customer requirements and expectations; evaluate and optimise a project design; design production systems and use them efficiently; and manage a variety of customised products. Rapid One-of-a-kind Product Development demonstrates how to develop new methods, tools and algorithms to address the problems in a mass customisation environment. It is a valuable source of information for researchers and engineers in the fields of design and manufacturing.
1. Motivation and Background -- 2. Review of Rapid OKP Product Development -- 3. Recent Development on Product Modelling -- 4. Integrated Product Development System for Rapid Product Development -- 5 Compound Method to Speed up the Sheet Metal Part/Product Development -- 7. Generic Product Modelling Framework -- 8. EXPRESS Data Model -- 9. Generic Product Modelling Framework: Case Study -- 10. Information Framework for Rapid Product Development -- 11 -- Product Development Cost Estimation and Optimisation -- 12. Integrated Data Structure for Supporting Rapid Product Development -- 13. Product Information Management System for Rapid and Integrated Mould Product Development -- 14. Internet Based DFX for Rapid Tool/Mould Making -- 15. Management of Product Process Knowledge in OKP Enterprises -- 16. Conclusions and Future Work.
Electronic reproduction.
Keywords: New products; Production planning; CAD/CAM systems; Sheet-metal work; Electronic books